Effect of the personality traits of healthy Japanese workers on depressive symptoms and social adaptation, and on the achievement rate of exercise therapy to prevent major depression - Ikenouchi, Atsuko; Okamoto, Naomichi; Matsumoto, Tomomi; Yoshimura, Reiji (Frontiers in Psychology, 2023)
Background This study determined the effects of personality traits on depressive symptoms and social adaptation in healthy workers, and the effects of depressive symptoms or social adaptation before and after exercise therapy, and personality traits before exercise therapy on the achievement rates of exercise therapy aimed at preventing major depression. Methods Two hundred fifty healthy Japanese workers were given an eight-week walking program as exercise therapy. After excluding 35 participants who had dropped or provided incomplete information, 215 were included in the analysis. The Japanese version of the NEO five-factor inventory was used to assess participants’ personality traits before the exercise therapy. Depressive symptoms were evaluated using the Japanese version of the Zung self-rating depression scale (SDS-J) and social adaptation was evaluated using the Japanese version of the social adaptation self-evaluation scale (SASS-J) before and after the exercise therapy. Results The SDS-J scores correlated with neuroticism and negatively correlated with extraversion, agreeableness, and conscientiousness before the exercise therapy. The SDS-J was also negatively correlated with openness in women, but not in men, while the SASS-J was associated with extraversion, openness, agreeableness, and conscientiousness, and negatively correlated with neuroticism. There was no significant change in levels of depression before and after exercise therapy; however, social adaptation increased significantly in men. No association was found between SDS-J and SASS-J scores before the exercise therapy and the achievement rate. The achievement rates of exercise therapy were negatively correlated with SDS-J or SASS-J after exercise therapy in women. The SDS-J after exercise therapy was correlated with neuroticism in men and negatively correlated with extraversion in women. The SASS-J after exercise therapy was negatively correlated with neuroticism and correlated with extraversion and openness in men. In contrast, the SASS-J after exercise therapy correlated with openness and agreeableness in women. Conscientiousness was correlated with the achievement rate of exercise therapy in men, but not with the various personality traits in women. Conclusion Depressive symptoms and social adaptation were differently associated with personality traits and achievement rates before and after exercise therapy. Conscientiousness before exercise therapy predicted a higher achievement rate for exercise therapy in men.